THE EXISTENCE AND DEVELOPMENT OF ISLAMIC LAW INSTITUTIONS IN INDONESIA - Hasbi Umar; Husin Bafadhal; Reza Rahmatullah (Universitas Nurul Jadid, 2025)
This study discusses the existence and development of Islamic legal institutions in Indonesia from historical, sociological, and juridical perspectives. Islamic law in the archipelago has been present since the early days of Islamization and has functioned in the areas of marriage, inheritance, and muamalah, although during the colonial period its role was narrowed through the theory of receptie. After independence, Islamic law gained formal legitimacy with the establishment of the Religious Court and was strengthened through various regulations, such as the Religious Court Law, the Compilation of Islamic Law, and legislation on zakat, waqf, and sharia economics. The research method used was qualitative with a historical-sociological approach, through literature review and descriptive-analytical analysis. The results of the study show that the process of integrating Islamic law into positive law took place gradually, from social norms to state law, and now has strong formal legitimacy in the national legal system. However, challenges in the form of legal dualism, social plurality, and harmonization with international law remain fundamental issues. Therefore, synergy between scholars, academics, and policymakers is needed to strengthen the position of Islamic law so that it remains relevant, applicable, and contributes to national legal development